Residual currents and transport pathways in the Tagus estuary, Portugal: the role of freshwater discharge and wind - Vaz, Nuno
Estuaries are interface areas between rivers and the coastal sea. They also receive point discharges of contaminants which can affect estuarine biogeochemistry. The study of residual circulation in estuaries is a key issue since it is related to the transport and dispersal of dissolved and non-dissolved substances. This study investigates the residual flows in a coastal plain estuary (the Tagus estuary, Portugal) taking into account the major forcing factors: tide, river discharge and wind stress. The methodology used is the implementation of a high resolution estuarine model in a 2D mode to simulate the tidal dynamics of the estuary. Tidal flows were calculated by tidally-averaging the flow currents along the whole estuary. The complex bathymetry of the estuary, tides, river discharge and wind stress modulate the residual flow in the Tagus estuary. The combine effect of the tide and river discharge creates preferential corridor flows in the deeper areas of the estuary. On the other hand, wind intensity and direction generate changes in residual currents in the shallow areas near the south shore of the estuary. River runoff changes the residual current intensity from values higher than 0.3 ms-1 (high discharge) to values of about 0.05 ms-1 (low discharge). The wind direction also induces changes in the residual flow patterns, inducing a rotation of the residual flow, according to the wind direction. Thus, the estuarine model of the Tagus estuary is a tool that sheds new insight about its fundamental hydrodynamics processes and consequently about the long term circulation patterns.